Análise multidimensional da infraestrutura das instituições de educação profissional tecnológica no Rio Grande do Sul (2021) - Pereira, Jaqueline Gomes (2023)
Access to education is a fundamental right and a necessary condition for citizenship, autonomy, and individual freedoms. Given the importance of providing quality education for socioeconomic development, this study aims to analyze the infrastructure of institutions for Professional and Technological Education in Rio Grande do Sul. To identify the origin and intensity of infrastructure deprivations, a multidimensional approach was adopted through the adaptation of the Alkire-Foster method. The multidimensional analysis allowed for a better evaluation of the context of the infrastructure of EPT institutions in Rio Grande do Sul, not only related to access and use of technology, but also to their basic conditions, access to human resources, among others. Thus, data and information were collected on the educational situation in Rio Grande do Sul, with a more detailed exploration of the microdata from the 2021 Basic Education School Census, in order to plan the data presentation. When planning the data presentation, 14 indicators describing the infrastructure conditions of the educational institutions in Rio Grande do Sul that had enrolled students in 2021 were analyzed, including federal, state, municipal, and private institutions. The study identified that federal institutions, according to the evaluated criteria, did not show any deprivations, which can be explained by the investments made in their infrastructure over the years. The School Infrastructure Deprivation Index (IPIE) for the state of Rio Grande do Sul was 9.19%. Among the institutions with higher IPIE were private institutions (16.50%), municipal institutions (8.30%), and state institutions (4.26%). The best performance among the indicators used in the estimation of IPIE was observed for the Access to basic services dimension. All 443 operating EPT institutions in 2021 had sanitary sewage. However, not all institutions have access to the Internet for use in teaching and learning processes – particularly 57.14% of state institutions. In the Basic school infrastructure dimension, 50% of municipal institutions lacked a library, and 94.73% of private institutions lacked a cafeteria. In the Pedagogical support dimension, private institutions showed 88% deprivation of laboratory assistants. Considering that the creation of socioeconomic opportunities and human development requires access to formal education systems, specific studies encompassing the scenario of institutions in Rio Grande do Sul are needed. With the purpose of monitoring educational policies and investments, it is important to conduct comparative studies between states over time.